(untitled) (Research, Society and Development, 2022)
This article starts from the concern about the students’ motivation to study Science, considering the relevance of this area of knowledge in the formation of subjects. Therefore, it aims to investigate the presence of intrinsic and extrinsic motivation and self-efficacy beliefs of 350 students belonging to the final years of Elementary School, from two public schools located in the city of Passo Fundo - RS. The research has a qualitative approach and comprised the application of questionnaires based on others already validated, which presented 14 assertions involving motivation in relation to Science and Science classes, which could be answered using a 5-point Likert scale. The results show that students feel motivated in Science classes, find it interesting, like and understand its importance for life, which exposes the presence of motivation and self-efficacy beliefs. However, extrinsic motivation stands out, where participants attributed importance to obtaining good grades, in addition to the importance of learning Science to achieve a good professional career.